RELASI ANTARA TIPE KEPRIBADIAN DAN PERKEMBANGAN KARAKTER MORAL PADA REMAJA - Susanna Kathryn; Boy Rio Sinaga (Edukasi : Jurnal Pendidikan Agama Kristen, 2023)
This study aims to explore the relationship between personality types and the development of moral character among adolescents using a qualitative constructivist approach. Data were collected through literature review and reflective analysis of school documents, then analyzed thematically. The findings reveal that conscientiousness and agreeableness traits positively support the development of moral character such as honesty, responsibility, and empathy, whereas neuroticism tends to hinder moral consistency. Traits of extraversion and openness to experience contribute uniquely by enhancing prosocial behavior and fostering acceptance of broader moral values. The study highlights that the development of adolescents’ moral character results from the interaction between internal factors (personality) and external factors (family, school, and cultural environment). It recommends that character education programs in both schools and families consider personality differences to improve the effectiveness of moral value internalization among adolescents.